Structural Model for Preparing Safe and Hygienic Complementary Food in Indonesia - Lucy Widasari; Anto J. Hadi; Haslinah Ahmad; Wirawan Setyalaksana; Lusy Damayanti; Elly Sutrisni (Journal of Public Health and Pharmacy)
Introduction: Early childhood nutrition is a fundamental determinant of optimal growth and development. The study aimed to evaluate how mothers provide complementary feeding (CF) to infants and young children aged 6–23 months. It explored factors influencing the adoption of safe and hygienic CF practices recommended by the WHO and Infant and Child Feeding Guidelines.